2022
DOI: 10.1037/tep0000376
|View full text |Cite
|
Sign up to set email alerts
|

The availability of training opportunities in personality disorders in American Psychological Association- and Psychological Clinical Science Accreditation System-accredited clinical and counseling psychology doctoral programs.

Abstract: Personality disorders (PDs) are relatively common, especially in clinical settings. A number of evidencebased treatments are now available, especially for borderline personality disorder (BPD). However, little is known about the relevant training available to doctoral students in clinical and counseling psychology. In the current study, data were extracted from 336 clinical and counseling PhD and PsyD programs from the Insider's Guide to Graduate Programs in Clinical and Counseling Psychology (Sayette & Norcro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This variation is consistent with state-level disparities in training in treating patients with personality difficulties; scholars have described a paucity of training and clinical practica in evidence-supported treatments for personality disorder. Scholars have found, for example, that training and practica in personality disorders has generally been found to be underrepresented in clinical psychology programs, with 16.4% of schools reporting at least one faculty member with a research interest in personality disorders and 14.9% offering a specific clinical practicum in treating PDs (Levy & Ellison, 2022). Without greater dissemination of EBTs in PDs, it is unclear that clinic directors will be able to provide comprehensive treatment and supervision for treating PDs in a day-treatment or residential setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variation is consistent with state-level disparities in training in treating patients with personality difficulties; scholars have described a paucity of training and clinical practica in evidence-supported treatments for personality disorder. Scholars have found, for example, that training and practica in personality disorders has generally been found to be underrepresented in clinical psychology programs, with 16.4% of schools reporting at least one faculty member with a research interest in personality disorders and 14.9% offering a specific clinical practicum in treating PDs (Levy & Ellison, 2022). Without greater dissemination of EBTs in PDs, it is unclear that clinic directors will be able to provide comprehensive treatment and supervision for treating PDs in a day-treatment or residential setting.…”
Section: Discussionmentioning
confidence: 99%
“…Growth in day-treatment programs may be related to greater interest in both internet-based training and delivery of DBT skills, which may provide for greater availability for clinicians to learn DBT principles, and for patients to receive DBT skills training (Frank et al, 2020; Lakeman et al, 2022). Additionally, training in DBT, at least among doctoral-level clinical psychology programs has been increasing during this time (see Levy & Ellison, 2022 vs. Magnavita et al, 2010). Levy and Ellison found a 129% increase in faculty with expertise personality disorders and a corresponding increase in clinic and externship clinical training in personality disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of modifications include the explication of a coherent model of the problem and treatment, a clear focus and priorities, an increased attention to explicit frame issues, vigilance for indications of colluding with the patient, acting out or iatrogenic behaviors on the therapist's part, provision of supervision or intervision, and integration with other services, among other aspects. These modifications require specific skills, and therefore clinicians who treat individuals with BPD should have training in one or more of the empirically supported treatments (but see Levy & Ellison, 2021), and employ evidence-based principles deriving from these treatments.…”
Section: Therapist Trainingmentioning
confidence: 99%
“…Most prevalence studies have found between 9% and 11% in community samples across multiple cultures and geographic areas (Winsper et al, 2019). A review of current prevalence work has shown that these rates increase sharply when using structured diagnostic measures in clinic populations (20-45% outpatient, 45%-50% inpatient; Levy & Ellison, 2021). Persons with PDs have been found to have increased service utilization, decreased functioning, and increased risk of suicide and suicidal behaviors relative to other psychiatric conditions such as major depressive disorder (Skodol et al, 2005).…”
mentioning
confidence: 99%